Apical Dimension of Root Canal Clinically Assessed with and without Periapical Lesions - Andrea Gesi; Paolo Mareschi; Tiziana Doldo; Marco Ferrari (International Journal of Dentistry)
To clinically evaluate the dimension of the more apical extent of the root canal after appropriate preflaring in the case of primary treatment and retreatment with and without the presence of periapical radiolucency, 392 single-rooted teeth with only one canal were evaluated during endodontic therapy. The canals were divided in two groups depending on the presence or absence of periapical radiolucency. After preflaring of the root canal the size of the root canal terminus (apical canal dimension) was gauged with hand-held Light Speed LS1 files inserted at the estimated working length and established with the use of an electronic apex locator. The dimension recorded in the computer database was represented by the largest instrument able to reach the electronically established working length. The differences between the treatment groups were assessed using the Mann-Whitney U test and the significance level was set at P<0.05. Teeth with lesions had a significantly greater diameter in the apical region than teeth without lesions (P<0.001). The dimension of the apical portion of the root canal is larger in the case of periapical radiolucency. This involves verifying this parameter in order to use the correct sized instruments and to obtain an efficient cutting action at the apical level.